Dynamic user profiles for web personalisation. Issue 5 (1st April 2015) - Hawalah, Ahmad; Fasli, Maria
Highlights We describe two algorithms for improving the mapping of interests to an ontology. We develop methods for modelling short and long-term user profiles. We introduce methods for adapting user profiles based on ongoing user behaviour. We demonstrate the effectiveness of our approach in a personalised search system.